Pregnancy in Women With Preexisting Glomerular Diseases: A Single-Center Experience - Marinaki, Smaragdi; Tsiakas, Stathis; Skalioti, Chrysanthi; Kapsia, Eleni; Lionaki, Sophia; Vallianou, Kalliopi; Boletis, John (Frontiers in Medicine, 2022)
Aim: Women with glomerular diseases are often of childbearing age. Besides lupus nephritis, data regarding pregnancy in patients with glomerular diseases are limited, posing a challenging task to attending nephrologists. This study aimed to investigate the pregnancy outcomes and the impact on the underlying glomerular disease among women followed in our institution. Methods: A single-center retrospective cohort study of women with biopsy-proven glomerular diseases who experienced pregnancy between 2010 and 2020. We analyzed data before, during and after gestation. Results: A total of 22 women, 13 with primary and 9 with secondary glomerular disease, were included in the study. Most patients (82%) had received immunosuppressive treatment at various times before pregnancy. All women were in remission, either complete (62%) or partial (38%), with well-preserved renal function (82%) before conception. A total of 30 live births and 1 stillbirth were recorded; the rate of preterm delivery was 23%. Renal function and proteinuria remained stable during pregnancy. Preeclampsia was observed in 6.7% of the patients and disease relapse in 6.9% of the pregnancies. Conclusion: Pregnancy was associated with good maternal and fetal outcomes in women with underlying glomerular diseases, provided they have a quiescent disease and preserved renal function.